Psychological predictors of engagement in music piracy - Brown, S.; Krause, Amanda (Routledge, 2017)
The digital revolution has changed how consumers engage with music. The present study explored the potential psychological factors underpinning why many consumers engage in music piracy. 396 participants (71.00% female, Mage= 34.53) completed an online questionnaire. Preference for accessing music digitally was associated with more favourable attitudes towards music piracy, as was being male, and expressing low levels of conscientiousness. Concerning the uses and gratifications of using different formats to engage with music, music piracy was found to be a financially viable way of listening to music. Discussion focuses on the notion that recorded music is perceived as poor value for money, and this is considered distinct from the widespread perception that piracy is simply about getting free music.